PENGARUH KUALITAS PRODUK DAN INOVASI PRODUK TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN PADA PRODUK KECANTIKAN MS GLOW DI KOTA PALEMBANG - Wanda Hamidah; Rismansyah Rismansyah; M Kurniawan (Universitas Nusa Cendana, 2023)
The purpose of this study was to determine the effect of product quality and product innovation on consumer purchasing decisions on MS GLOW beauty products in the city of Palembang. The method used in this study are coefficient of correlation, coefficient of determination analysis, and hypothesis testing using the SPSS22 software program for Windows. The results of the t-test show that there is a partial influence between the variables of product quality and product innovation on purchasing decisions, and the F-test shows a significant effect on the variables of product innovation simultaneously on consumer purchase decisions on MS Glow Beauty products in Palembang. Keywords: Product Quality; Product Innovation; Purchasing Decisions